Development and Psychometric Evaluation of the Moral Commitment Scale for Thai Baccalaureate Nursing Students (MCS-Thai) - Chutima Perngyai (Prince of Songkla University, 2023)
Thesis (Ph.D., Nursing (International program))--Prince of Songkla University, 2018